Elaboración de productos de chocolatería a partir del cacao - Cumapa Vásquez, Luis Porfirio (2015)
Chocolate products are generally foods whose main raw material is the cocoa bean (Theobroma cacao). After various operations such as fermentation, drying, cleaning, sorting, roasting, hulling, and grinding, the original ingredients of chocolate are obtained. 0.5% of cocoa butter is lost during roasting because the heat causes the cocoa butter to melt. This means that some remains free enough to migrate to the shell, where it remains and is discarded during hulling. In grinding cocoa beans, there are two objectives: The first is to make the cocoa particles small enough to facilitate chocolate making. The second, even more important, is to extract the largest amount of fat from the interior of the cocoa bean, called the cotyledon. This fat is necessary to facilitate the flow of chocolate, since when crystallized in small quantities, it facilitates the solidification of the chocolate. The production of chocolate products basically involves ingredients such as cocoa liquor, also called cocoa paste, cocoa butter, sugar, and, to a lesser extent, an emulsifier called lecithin. Milk, almonds, peanuts, etc. can also be added. This depends on the type of chocolate being made and individual taste. Even a minimal amount of water is considered undesirable in chocolate making because the sugar particles would begin to stick together, thus increasing viscosity, making the process more difficult.